Spike is the most recognized antigen in the whole-blood platform in both acute and convalescent COVID-19 patients. (May 2021) - Aiello, Alessandra; Najafi Fard, Saeid; Petruccioli, Elisa; Petrone, Linda; Vanini, Valentina; Farroni, Chiara; Cuzzi, Gilda; Navarra, Assunta; Gualano, Gina; Mosti, Silvia; Pierelli, Luca; Nicastri, Emanuele; et al.
Highlights: Whole-blood interferon-γ-release assay (IGRA) enabled the response to SARS-CoV-2 peptides to be evaluated. Spike protein was the best stimulus to discriminate COVID-19 from NO-COVID-19. A SARS-CoV-2-specific response is rarely observed in NO-COVID-19 individuals. This SARS-CoV-2 IGRA has the potential to be a powerful diagnostic tool. Abstract: Objectives: To identify the best experimental approach to detect a SARS-CoV-2-specific T cell response using a whole-blood platform. Methods: Whole-blood from 56 COVID-19 and 23 "NO-COVID-19" individuals were stimulated overnight with different concentrations (0.1 or 1 μg/mL) of SARS-CoV-2 PepTivator® Peptide Pools, including spike (pool S), nucleocapsid (pool N), membrane (pool M), and a MegaPool (MP) of these three peptide pools. ELISA was used to analyse interferon (IFN)-γ levels. Results: The IFN-γ-response to every SARS-CoV-2 peptide pool was significantly increased in COVID-19 patients compared with NO-COVID-19 individuals. Pool S and MegaPool were the most potent immunogenic stimuli (median: 0.51, IQR: 0.14–2.17; and median: 1.18, IQR: 0.27–4.72, respectively) compared with pools N and M (median: 0.22, IQR: 0.032–1.26; and median: 0.22, IQR: 0.01−0.71, respectively). The whole-blood test based on pool S and MegaPool showed a good sensitivity of 77% and a high specificity of 96%. The IFN-γ-response was mediated by both CD4 + and CD8 + T cells, and independently detected of clinical parameters in both hospitalized and recovered patients. Conclusions: This easy-to-use assay for detecting SARS-CoV-2-specific T cell responses may be implemented in clinical laboratories as a powerful diagnostic tool.